2016
DOI: 10.2147/cia.s119241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of prostate artery embolization on lower urinary tract symptoms related to benign prostatic hyperplasia: a systematic review and meta-analysis

Abstract: BackgroundProstate artery embolization (PAE) is emerging and is a promising minimally invasive therapy that improves lower urinary tract symptoms (LUTS) related to benign prostatic hyperplasia (BPH). The purpose of this article was to evaluate the efficacy and safety of PAE on LUTS related to BPH.Materials and methodsA literature review was performed to identify all published articles of PAE for BPH. The sources included MEDLINE, EMBASE and Cochrane Library from 1980 to 2016. A systematic review and meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 21 publications
3
19
1
6
Order By: Relevance
“…None of the reviewed studies showed a decrease in IIEF score after PAE. Three meta-analyses of PAE (51,54,56) showed slight improvement of IIEF score after PAE, whereas 2 meta-analyses (52,55) showed no change. The 3 RCTs of PAE (28)(29)(30) showed no change in IIEF score following PAE.…”
Section: Safety Of Paementioning
confidence: 97%
See 1 more Smart Citation
“…None of the reviewed studies showed a decrease in IIEF score after PAE. Three meta-analyses of PAE (51,54,56) showed slight improvement of IIEF score after PAE, whereas 2 meta-analyses (52,55) showed no change. The 3 RCTs of PAE (28)(29)(30) showed no change in IIEF score following PAE.…”
Section: Safety Of Paementioning
confidence: 97%
“…Six meta-analyses of PAE for BPH have been published (51)(52)(53)(54)(55)(56). The largest and most recent (51) was a systematic review of trials studying the efficacy of PAE to treat LUTS, performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, with a meta-analysis done using the random-effects model.…”
Section: Meta-analysesmentioning
confidence: 99%
“…Özellikle çok büyük hacimli prostatı ya da median lob hipertrofisi olan hastalarda işlemden sonra akut üriner retansiyon görülebilir (%7-9).Bu durumda hasta sondalanmalı ve 3-5 gün sonda ile takip edilmelidir. Literatürdeki tüm çalışmalarda işlem sonrası üriner retansiyon geliştiren tüm hastalarda 1. haftada spontan idrar çıkışı gözlemlenmiştir [47][48][49][50].…”
Section: İstenmeyen Etkiler Ve Komplikasyonlarunclassified
“…Hayatı tehdit edici majör komplikasyon şu ana kadar literatürde bildirilmemiştir. Bunun dışında da erektil disfonksiyon ya da retrograd ejakü-lasyon hiçbir seride tanımlanmamıştır [48][49][50][51][52][53].…”
Section: İstenmeyen Etkiler Ve Komplikasyonlarunclassified
“…Prostate artery embolization (PAE) is a new minimally invasive procedure [8], non-invasive to the urinary system and possible to perform as day-care treatment.…”
Section: Introductionmentioning
confidence: 99%